Amphora stamps from Philippopolis in Thrace. A new approach to the identification of the Dressel 24/ Dressel 24 similis type production areas - Borislavova, Nadezhda (Rei Cretariae Romanae Fautorum Acta, 2023)
This paper presents stamped amphorae Dressel 24/Dressel 24 similis type, discovered during archaeological excavations in Philippopolis – a major redistributive center of the intra-provincial trade in Roman Thrace. The names on the stamps of these olive oil amphorae are usually interpreted as names of officinatores. In this article, it is suggested that they belong to eponymous officials, as the same names can be found on the reverse of provincial coins issued by the cities in western Asia Minor. Reconsideration of the epigraphic data offers a new perspective on identifying the Dressel 24/ Dressel 24 similis type production areas. Further investigation of the chronology and typological features of the type allows linking its variants to a certain region of origin – the city on whose territory the olive oil was produced and precise date – as the office of the eponym was mandated.